EFFECT OF HOUSING ON PERFORMANCE AND BLOOD BIOCHEMICAL TRAITS OF CHICKEN IN MEGHALAYA (Indian Journal of Animal Production and Management, 2015)
The experiment was carried out to study the effect of deep litter and raised floor housing systems on the performance and blood-biochemical parameters in Vanaraja, Gramapriya and Indigenous grower chickens (9-18 weeks) in the agro-climatic condition of Meghalaya during summer (March to July) season. Different weather parameters like temperature, humidity and rainfall were recorded during the experimental period. The body weight gain (g/day/bird), FCR and mortality(%) recorded under deep litter system were 15.58±1.26, 3.51±0.17 and 4.03±0.49 respectively; whereas the corresponding values under raised floor system were 18.29±1.69, 3.2±0.15 and 2.85±0.38 respectively. System of housing had no significant effect on blood biochemical traits. The results revealed that the birds under raised floor system performed better than the birds under deep litter system which indicated that the raised floor system would be better during summer for grower birds in the climatic condition of Meghalaya.
Keywords: Housing Systems; performance; biochemical; Vanaraja; Gramapriy; Indigenous